Primary intraosseous malignant peripheral nerve sheath tumor of metacarpal bones of the hand in a patient without neurofibromatosis 1: Report of a rare case - Bharti Devnani; Ahitagni Biswas; Sameer Bakhshi; Shah Alam Khan; Asit Ranjan Mridha; Shipra Agarwal (Indian Journal of Medical and Paediatric Oncology)
Malignant peripheral nerve sheath tumor (MPNST) usually arises in peripheral nerve sheath cells. The intraosseous location of MPNST is rare. Mandible is the most common site of bony involvement. Involvement of bones of the hand is quite unusual. We report a case of MPNST involving metacarpal bones of the left hand treated with surgery followed by adjuvant radiation and chemotherapy and review the pertinent literature.